2022
DOI: 10.1055/a-1789-2762
|View full text |Cite
|
Sign up to set email alerts
|

Verfügbarkeit von Medikamenten für die Behandlung von Katzen mit Augenerkrankungen in Deutschland – Diskrepanz zwischen Theorie und Wirklichkeit

Abstract: Zusammenfassung Gegenstand und Ziel Es gibt nur wenige Ophthalmologika, die speziell für Katzen zugelassen sind, weshalb häufig humanmedizinische Arzneimittel angewandt werden. Die Anwendung, Umwidmung, Abgabe und Verschreibung von Arzneimitteln ist in Deutschland durch das Arzneimittelgesetz (AMG) und die Verordnung über tierärztliche Hausapotheken (TÄHAV) geregelt. Ziel dieser Studie war es, Daten über das Vorkommen und die Häufigkeit von Erkrankungen des Katzenauges zu gewinnen sowie die Häuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Despite the previous fact, ELDU is still essential in the veterinary field. For instance, a recent German study confirmed that ELDU is necessary for 68.8% of cats suffering from ocular diseases, from which 96.8% received human-approved pharmaceuticals [ 36 ]. Another recent report stated that The Canadian Global Food Animal Residue Avoidance Databank receives over 2300 annual requests from licensed veterinarians, with ~65% requesting the use of extra-label drug combinations in poultry feed [ 37 ].…”
Section: Sources Of Drug Residues In Farm Animalsmentioning
confidence: 99%
“…Despite the previous fact, ELDU is still essential in the veterinary field. For instance, a recent German study confirmed that ELDU is necessary for 68.8% of cats suffering from ocular diseases, from which 96.8% received human-approved pharmaceuticals [ 36 ]. Another recent report stated that The Canadian Global Food Animal Residue Avoidance Databank receives over 2300 annual requests from licensed veterinarians, with ~65% requesting the use of extra-label drug combinations in poultry feed [ 37 ].…”
Section: Sources Of Drug Residues In Farm Animalsmentioning
confidence: 99%